Consciousness of newborns and infants: from instinct to developmental indicators - Boltivets, Serhiy; Honchar, Oleksiy; Uralova, Lyudmyla (Psyhology & society, 2019)
The research highlights an experience of methodologization in the sphere of psychology that belongs to theoretical foundations of human consciousness in ontogenesis and encompasses the psychophysical dimensions of its life functioning. The peculiarities of genetically primary forms of human consciousness development, based on organic instincts as possibilities of future psycho-physiological self-realization of newborns and infants, are highlighted. The conceptual definition of consciousness, which essentially consists in the mutual awareness of oneself, and therefore the correlation with our own life, which is the mission of survival-creation, common to all living beings. It is shown that the emergence of consciousness is a path of early development of the human organism, the ontogenesis of which begins with an assignative period of silence. The correlation of ontogenesis with philogenesis is carried out, which reveals the immediate precondition of consciousness by the development of its expressive means, both verbal and nonverbal, but mainly centered on the development of language and speech as a process of language application under specific conditions of social interaction of a person. The fact-regularity of uninterrupted process of expanding consciousness was substantiated, which takes place as a step from the specific to its general meaning, where the last one is always connected with the feeling of action, movement, awareness of this leads to their transformation into an image corresponding to action, movement or act in a conditional, sign meaning, suitable for future  multiple deployment. The reproduction of philogenesis in ontogenesis is presented as an important evidence of conformity, and hence the truth of methodology of neurosonography to identify the features of the development of the infant’s consciousness, since the sound expression of consciousness at the speech stage of human life preceded by the period inherent in the infant. Highly competent medical and psychologically oriented consciousness operates with a certain model of the possibilities of psycho-physiological forecast of newborn babies’ development during a time, when the front crown of the head is still open. The psychophysical factors of these possibilities are related to the indications, since there are no contraindications to the use of neurosonography. Neurosonographic examination increases the probability of diagnosing a significant number of pathological changes in the brain in newborns and infants, which can be visualized with the help of ultrasound as a biopsychic basis for the future consciousness of an adult and mature person. The methodological scheme of a professional psychological experience that is disclosed in the study is based on the fundamental tenacity of uninterrupted variability of individual models, the differences between which can largely dominate the common features, which will constitute the inevitable way of awareness - the semantic enrichment of the personality consciousness. The world of both individual consciousness of human, and collective consciousness of a nation requires the preservation of it as an integrity, without which the existence of any subject of social self-movement and creative self-realization  is impossible. The fundamental difference between methodological optics in its ideological, psychological and neurosonographic, purely physical, expressions is apparent, since differences depend on many factors of human perception (worldview, experience, and potentiality) and, at the same time, its neurosonographic embodiment enters to a philosophical methodology that can not be integrity without its own physical realization. The methodological integrity of the physical optics of neurosonography is based on this physical realization, determining the forecast of life-long development of capacities of newborns and infants’ psychophysical possibilities. The prospects of these studies are in the embodiment of the psychological function of collective memory and the implementation of diagnostic visualization of psychophysical instincts of children’s and adults’ development of consciousness.